(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: to assess knowledge of health report statistics among commune health station staff in Hau Loc and Quang Xuong districts, Thanh Hoa Province, and to examine related factors. Methodology: A cross-sectional study was conducted at 48 commune health stations in Hau Loc and Quang Xuong districts from January 2024 to February 2025. Data were collected via a standardized questionnaire developed based on healthcare regulations and expert input. Results: Of the 234 participants (response rate: 83,5%), 57.3% demonstrated adequate knowledge of health report statistics. Knowledge levels were significantly higher in Quang Xuong (63.4%) than in Hau Loc (36.6%, p<0.001). In Hau Loc, staff with 11–20 years of experience were more likely to have adequate knowledge compared to those with 1–10 years (OR: 3.59; 95% CI: 1.18–10.93; p=0.024). However, staff without statistical training or guidance on primary healthcare management software were significantly less likely to exhibit adequate knowledge. Conclusion: Knowledge of health report statistics among commune health station staff varies regionally, with lower levels in Hau Loc, particularly among staff with less experience, no training, or insufficient software guidance. These findings underscore the need for ongoing training and practical software support to strengthen professional skills, enhance data accuracy, and optimize primary healthcare system performance.